2019
DOI: 10.15625/1859-3097/19/2/10814
|View full text |Cite
|
Sign up to set email alerts
|

A study on bacteria associated with three hard coral species from Ninh Thuan waters by epifluorescence and most diluted culture method

Abstract: Coral associated bacteria and their host are currently one of the interested issues for research and scientists worldwide. The densities of zooxanthellae and bacteria associated with three most prevalent species Acropora hyacinthus, Acropora muricata and Acropora robusta in Hang Rai, Ninh Thuan was evaluated over time by staining with SYBR Gold and direct counting with epifluorescence method. The most dominant bacteria were isolated by culture dependent method. The densities of zooxanthellae and bacteria range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Coral samples were collected in May, June, August 2016, and June 2017 by skilled divers (SCUBA) at a depth of 5-7 m at the location at coordinates 109 o 18'28.1"E, 11 o 67'71.7"N, at Hang Rai-Ninh Thuan. The method of sample collection and pretreatment of samples, and analysis of samples and environmental factors are detailed in our previous study [17]. The symbiotic algae, bacteria in healthy coral samples, and bleached coral samples were treated with 1% potassium citrate solution to remove the fluorescent colorants available in corals, then filtered through a 0.02 µm filter (AnodiscTM Whatman) and stained with SYBR Gold (Invitrogen) [18] and examined under a fluorescence optical microscope.…”
Section: Materials and Research Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coral samples were collected in May, June, August 2016, and June 2017 by skilled divers (SCUBA) at a depth of 5-7 m at the location at coordinates 109 o 18'28.1"E, 11 o 67'71.7"N, at Hang Rai-Ninh Thuan. The method of sample collection and pretreatment of samples, and analysis of samples and environmental factors are detailed in our previous study [17]. The symbiotic algae, bacteria in healthy coral samples, and bleached coral samples were treated with 1% potassium citrate solution to remove the fluorescent colorants available in corals, then filtered through a 0.02 µm filter (AnodiscTM Whatman) and stained with SYBR Gold (Invitrogen) [18] and examined under a fluorescence optical microscope.…”
Section: Materials and Research Methodsmentioning
confidence: 99%
“…In August 2016, with the lowest PO 4 concentration, bacteria and bacilli increased to overwhelm cocci. Bacteria living on corals of bacilli and bacilli group were negatively correlated [17] with PO 4 content. In contrast, the proportion of cocci and bacilli in water samples over the months did not change significantly, and Anova's test showed that this difference is also not statistically significant (p > 0.05).…”
Section: Total Number Of Heterotrophic Bacteriamentioning
confidence: 98%